Leadership and conflict management in production organisations - Glavaš, Jerko (Array, 2019)
Conflicts between different interests are inevitable in every business organization. Therefore, it is not surprising that the number and intensity of conflicts is sometimes very high. Conflict resolution is a skill without which managers can hardly succeed in their business. The subject of research in this paper is conflict management from a technical and economic point of view. The paper defines and analyzes the notion of leadership, that is, elements and dimensions of leadership, the notion of leader, and theoretical approaches to leadership. In addition to the above, the concept of conflict, more specifically its type, levels of conflict, consequences and causes, and techniques of conflict resolution have been defined and analyzed. An online survey (based on the LinkedIn Business Social Network) was conducted to determine how individuals in a production organization respond and resolve conflicts as well as the results of the same. Based on theoretical scientific approach, the conducted research and the analysis of the results, conclusions and recommendations are given, as well as key questions for future research.